PENGARUH CITRA TOKO TERHADAP KEPUASAN PELANGGAN DAN NIAT BELI ULANG PADA CIRCLE K DI KOTA DENPASAR - Yulianti, Ni Made Dhian Rani; Suprapti, Ni Wayan Sri; Yasa, Ni Nyoman Kerti (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 8 Nomor 1 Tahun 2014)
This study aimed to determine the effect of store image on customer satisfaction, the influence of satisfaction on customer repurchase intention, and effect of store image on customer repurchase intention. Data collected through the survey by distributing questionnaires to 185 respondents. Data were analyzed using SEM with application software AMOS and SPSS. The results showed that: (1) Store image has a positive and significant impact on customer satisfaction. (2) Customer satisfaction has a positive and significant impact on customer repurchase intention. (3) The store image has a positive and significant impact on customer repurchase intention
Keywords: store image, satisfaction, and repurchase intention